Advertising Media p.lanning - Larry D kELLY ([Place of publication not identified] : Routledge, 2022)
Advertising Media p.lanning blends the latest methods for digital communication and an understanding of the global landscap.e with the best p.ractices of the functional areas of media p.lanning. Taking a unique brand communication ap.p.roach from an agency p.ersp.ective, the textbook is organized into four key p.arts, walking the student through the foundations of brand communication, communication p.lanning, the different media channels available, and the p.rocess of p.rep.aring, p.resenting, and evaluating a media p.lan.This 5th edition...
Keywords: MEDIA